Нужный справочник домашнего мастера: справочное издание / сост. А. М. Горбов - Горбов Александр Михайлович (АСТ, 2008)
Экземпляры: ОРФ (2009) / Инвентарный номер: 45328 / Цена: / Сис.шифр: 37 / Авт.знак: Н 88 / ББК: 37.279я2